Zinc nutrition and dietary zinc supplements. Issue 9 (3rd April 2023) - Duan, Maoping; Li, Tian; Liu, Bo; Yin, Shuhua; Zang, Jiachen; Lv, Chenyan; Zhao, Guanghua; Zhang, Tuo
Abstract: As the second most abundant trace element in the human body, zinc nutrition is constantly a hot topic. More than one-third population is suffering zinc deficiency, which results in various types of diseases or nutritional deficiencies. Traditional ways of zinc supplementation seem with low absorption rates and significant side effects. Zinc supplements with dietary components are easily accessible and improve zinc utilization rate significantly. Also, mechanisms of maintaining zinc homeostasis are of broad interest. The present review focuses on zinc nutrition in human health in inductive methods. Mainly elaborate on different diseases relating to zinc disorder, highlighting the impact on the immune system and the recent COVID-19. Then raise food-derived zinc-binding compounds, including protein, peptide, polysaccharide, and polyphenol, and also analyze their possibilities to serve as zinc complementary. Finally, illustrate the way to maintain zinc homeostasis and the corresponding mechanisms. The review provides data information for maintaining zinc homeostasis with the food-derived matrix.